The biosensing performance and electrochemical properties of carbonised electrospun nanofiber - Shafiei, Ahmad Deedat (2019)
This research project is important in order to study the performance of biosensing technology toward carbonised electrospun nanofiber. Biosensor is one of the most important analytical devices to be used in analysing analyte where the analyte is referring to any substance whose chemical constituents are being identified and measured. There are few available biosensors that is commonly used such as glucose monitoring device that works to monitor glucose level in human blood of a diabetic patient. There are several compulsory components to make up a fully functional biosensor. By principle, a biosensor must consist of sample, analyte, bioreceptor and transducer. Transducer plays an important role in biosensing as it converts physical quantitative and qualitative measurement and convert those values into electrical signal. Transducer is also known as sensing platform. In order transducer to become biologically capable in detecting the presence of analyte, bioreceptors or biosensing elements are required to be integrated with the support of transducer. In this research, our main concern is to find the best type of electrospun nanofiber that will be used to become the support for the transducer of the glucose monitoring biosensor. Thus, there were several PAA/PAN-based electrospun nanofibers used and each of the nanofibers has different associated nanoparticle fabricated together with the PAA/PAN polymer. The nanofibers were used to be immobilised with (GOx) enzyme. (GOx) enzyme is the biosensing element which detect the presence of glucose. Biosensing performance of the electrospun nanofiber that has been used is reflecting conductivity of the nanofiber itself. Better conductivity gives better electrochemical properties and biosensing ability. The biosensing performance were analysed by using several analyses mainly electro impedence spectroscopy (EIS), capacitance-voltage profiling (CV-plot) which consist of scan rate dependent study with potassium ferrocyanide solution. As the result, Sample (2) PAA/PAN rGONps had showed the suitable nanofiber to fabricate a biosensor as it the most conductive nanofiber and has good electrochemical properties due to its responsiveness to interact with electrolyte and analyte. Sample (C) PAA/PAN AuNps in the second place is also a suitable nanofiber for a biosensor.